An Analytical Approach for Estimation of Customers Priority towards Brand Preferences in Modern Retailing Organizations - Prasanna kumar, SS. Asadi3, B. Suresh (International Journal of Advanced Science and Technology, 2020)
Retailing consists of all activities involved in the marketing of products directly to the consumers for their personal, family, or household consumption. It is however, imperative to identify the fact that in today’s world of multifaceted trade, the function of retailing would include not just goods but services too, which may be provided to the final consumer. In an age where the customer is regarded as the king and marketers are aiming for customer delight, retail may be redefined as the first point of customer contact. Over the last few decades, the world of retailing has seen a tremendous change.